Pension system design and intergenerational redistribution: applying Musgrave’s rule in a comparative setting (Szociológiai Szemle, 2023)
This paper focusses on the intergenerational distribution of risk and burden of pension financing in differing pension systems. We apply the Musgrave rule of intergenerational fairness, which proposes a pension system to be fair across generations when the system produces a fixed ratio of pensions and labour earnings. By comparing pension system design and the financing of pension provision in eight European countries, the effects of the institutional set-up of pension systems on intergenerational redistribution are assessed, including the key features of the pension systems such as the financing and reform trends of recent years that have affected their intergenerational fairness. By including both statutory and occupational pension schemes in our analysis, we extend the Musgrave framework to cover the most relevant schemes for pension provision. Pension systems address intergenerationally fair redistribution to varying degrees depending on their design as defined benefit (DB) or defined contribution (DC) schemes and their mixture of statutory and occupational components. The current trend in pension design implies less intergenerational risk sharing within the pension system and less redistribution from workers to retirees. Our results show that current retirees are rather well protected. The contribution burden caused by demographic ageing and growth in pension expenditure is not directly imposed on current employees, but tax financing is gaining in importance in many countries.